Survey of the Role of Emigrant Artists and Craftsmen in the Flourishing of the Civilization of the Timur's Era - Maryam Salehikia; Ahmad Salehi Kakhki; Mitra Shateri (هنرهای زیبا. هنرهای تجسمی)
The Timurid period is one of Iran's most brilliant periods of Civilization and culture, though he was one of the cruelest rulers of Iran, and during his thirty-six-year reign, he suppressed competitors and rebels and established a powerful government. In spite of this fact, Timur is known for his extensive support of art and industry. Referring to the numerous reports of historians, during Timur's campaigns and conquests, prominent and famous artists and craftsmen of each city were protected from the damage of the soldiers, and they were sent to Samarkand to implement his major and ambitious projects. Achieving the huge wealth and skilled manpower of the conquered lands provided favorable conditions for the flourishing of the arts and handicrafts. The purposes of this research are to survey the role of immigrant artists and craftsmen in the flourishing of Timur’s era civilization and determine their origin and expertise. An attempt is made to answer these questions that, according to historical texts and archaeological data, which areas artists and craftsmen Timur sent to Transoxiana? What were their specialties, and in what fields were they employed? The information collection is desk-based, and the research method is historical-analytical. The results indicate that most of the artists and craftsmen were moved to Samarkand from Shiraz, Isfahan, Tabriz, Baghdad, Damascus, and Delhi. Due to numerous reports of historical texts, masters, architects, and engineers of conquered lands participated in the construction of great buildings such as the Aq Sara Palace in Shahr-i-Sabz and the Samarkand Jame' Mosque and the signatures of architects from Shiraz, Isfahan, and Tabriz in the Timur's buildings, confirms these reports. According to Muzaffarid Monuments in Isfahan, Yazd, and Kerman, it can be concluded that Al-Muzaffar architecture played a prominent role in the formation of Timurid architecture, and the migration of artists from Shiraz and Isfahan caused the transfer of this architectural style from the central and southern regions of Iran to Transoxiana. Timurid architecture has inherited features such as the double-layer dome and especially mosaic tile. Timur also sent several prominent calligraphers from conquered areas to Samarkand. They were engaged in writing official letters and Qur'anic manuscripts, and according to their remaining signatures, they also wrote the inscriptions of the buildings. Immigrant painters also performed the wall paintings of his palaces. According to Timur's successive campaigns, the supply of weapons was very important and essential, and the metalworkers who gathered in Samarkand, especially from Damascus and Turkey, often made cannons, helmets, armor, and bows and arrows. The signatures of the artists engraved on the cauldrons, candlesticks, and doorknocker in the tomb of Khwaja Ahmad Yesavi in Turkestan confirm the migration of metalworkers from Tabriz and Isfahan to Transoxiana in the Timur era.